The Stem Cell State in Plant Development and in Response to Stress - Grafi, Gideon; Florentin, Assa; Ransbotyn, Vanessa; Morgenstern, Yakov (Frontiers in Plant Science, 2011)
Stem cells are commonly defined by their developmental capabilities, namely, self-renewal and multitype differentiation, yet the biology of stem cells and their inherent features both in plants and animals are only beginning to be elucidated. In this review article we highlight the stem cell state in plants (with reference to animals) and the plastic nature of plant somatic cells (often referred to as totipotency) as well as the essence of cellular dedifferentiation. Based on recent published data, we illustrate the picture of stem cells with emphasis on their open chromatin conformation. We discuss the process of dedifferentiation and highlight its transient nature, its distinction from reentry into the cell cycle and its activation following exposure to stress. We also discuss the potential hazard that can be brought about by stress-induced dedifferentiation and its major impact on the genome, which can undergo stochastic, abnormal reorganization leading to genetic variation by means of DNA transposition and/or DNA recombination.